Urban-rural differences in immune responses to mycobacterial and tetanus vaccine antigens in a tropical setting: A role for helminths? - Kabagenyi, Joyce (Parasitol Int, 2020)
Several vaccines elicit lower efficacy or impaired immune responses in rural compared to urban settings, and in tropical low-income countries compared to high-income countries. An unresolved hypothesis is that immunomodulation by parasitic infections such as helminths (prevalent in rural tropical settings) contributes to suppression of vaccine responses. Among 1–17-year-old Ugandan residents of rural Schistosoma mansoni (Sm)-endemic islands and proximate urban communities with lower helminth exposure, we assessed plasma antibody and whole blood assay cytokine responses to tetanus toxoid (TT) and purified protein derivative of Mycobacterium tuberculosis (PPD). These were taken to represent recall responses to tetanus and BCG vaccination in infancy. PPD-specific responses are additionally induced by tuberculous and non-tuberculous mycobacterial exposure. Urban-rural comparisons showed that PPD-specific IFN-γ and IL-13 and TT-specific IL-13 and IgG concentrations were lower in the rural setting, but that PPD-specific IgE concentrations were higher. Among rural participants, Sm infection was inversely associated with PPD-specific IFN-γ, while nematode infection was positively associated with PPD-specific IgG. Among urban participants, Sm infection was positively associated with PPD-specific responses but inversely associated with TT-specific responses, while nematode infection was inversely associated with TT-specific IgG and IgG4, but no associations were observed with PPD-specific responses. Despite these associations, for the urban-rural comparisons there were no notable changes in test statistics after adjusting for current helminth infections, suggesting that helminths were not the sole explanation for the urban-rural differences observed. Helminths likely work in concert with other environmental exposures and operational factors to influence vaccine response.